Serum vascular endothelial growth factor (VEGF) levels correlate with number and location of micrometastases in a murine model of uveal melanoma - Crosby, Michelle B (BMJ Group, 2010)
BACKGROUND: A preliminary animal study was performed to determine if hepatic micrometastases from uveal melanoma secrete vascular endothelial growth factor (VEGF) that is measurable in serum. METHODS: We analysed the serum of a C57Bl/6 mouse model of uveal melanoma (n=10) at days 4, 7, 14 and 21 post-inoculation for VEGF levels. We compared the serum VEGF levels with the number and location of hepatic micrometastases and their respective expression of VEGF mRNA. RESULTS: Serum VEGF levels rose after inoculation of C57Bl/6 mice eyes with B16LS9 cutaneous melanoma cells. Beginning on day 14 there was a statistically significant (p<0.05) increase in VEGF levels, rising to an average peak level of 37.985 pg/ml at day 21. Peak serum VEGF levels correlated with the total number of hepatic micrometastases (R=0.444) and there was moderate correlation of peak VEGF serum levels with micrometastases in more hypoxic locations (R=0.572). VEGF mRNA expression by micrometastases was highest in the most hypoxic regions of the hepatic lobule. CONCLUSIONS: Hepatic micrometastastic melanoma arising in a mouse model of ocular melanoma secretes VEGF. The number and location of the micrometastases correlate with serum VEGF levels.